Analysis of the upshot of heat treatment on physical and mechanical behavior of aluminum hybrid composites. (2022) - Veeranaath, V.; Daga, Uddhav; Sharma, Pranay; Kumar, Yuvraj
Abstract: In the current scenario, aluminum-based composites are gaining a considerable volume of importance owing to their wide applications and needs. This article is chiefly fixated on the production of aluminum-based hybrid composites by the stir casting route. Aluminum alloy Al 6061 was used as the matrix phase and the reinforcements like alumina and graphite were taken for the processing of composites. In this investigation, the processing constraints like reinforcement (wt.%), stirring time, and stirring speed were varied in 2 levels and the L4 Taguchi array has been employed for the experiment. The developed four samples were also subjected to different types of heat treatment like annealing, normalizing, tempering, and quenching to study the upshot of the same on its behavior. The characteristics like density, hardness, and wear were studied, compared, and analyzed before and after the heat treatment of samples. Data were analyzed and optimized using Taguchi analysis to mainly learn the significance of processing constraints on the output properties. The results indicated that heat treatment has a considerable effect on density and wear but a very little effect only on hardness.